New Method for Image Encryption Using GOST And Chaotic Tent Map - Yahi, Amina; Bekkouche, Tewfik; Diffellah, Nacira (University of Eloued جامعة الوادي, 2022)
This research paper proposes a simple and an efficient image encryption scheme based on chaotic tent map and GOST algorithm, which is the Russian norm of encryption. The tent chaotic system was used to generate chaotic random keys, as well as a chaotic shift values that used in the GOST algorithm, in order to provide security as a higher strength. The obtained simulation results prove the performances of the proposed method in term of histograms analysis data loss and sensitivity test.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Encryption· Tent chaotic map· Image· GOST.